2018
DOI: 10.1038/s41416-018-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Immune dysregulation in cancer patients developing immune-related adverse events

Abstract: BackgroundUp to 40% of cancer patients on immune checkpoint inhibitors develop clinically significant immune-related adverse events (irAEs). The role of host immune status and function in predisposing patients to the development of irAEs remains unknown.MethodsSera from 65 patients receiving immune checkpoint inhibitors and 13 healthy controls were evaluated for 40 cytokines at pre-treatment, after 2–3 weeks and after 6 weeks and analysed for correlation with the development of irAEs.ResultsOf the 65 cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 30 publications
4
112
0
1
Order By: Relevance
“…A rise of serum IL-6 levels was associated with immune-related adverse events as well as with release of tumor marker in the majority of the treated melanoma patients presented in this study. A study from 2019 analyzed the correlation of different cytokines including IL-6 and irAE during checkpoint inhibitor treatment of various cancers on a two to three weeks basis and identified that the irAE group (n = 16) had significantly elevated levels of five cytokines (IL-6, CXCL2, CCL20, CXCL8 and CCL23) compared to healthy controls [44]. Moreover, the authors stated that the increase in cytokines/chemokines at two-three weeks and at six weeks was significantly greater in the irAE group.…”
Section: Discussionmentioning
confidence: 99%
“…A rise of serum IL-6 levels was associated with immune-related adverse events as well as with release of tumor marker in the majority of the treated melanoma patients presented in this study. A study from 2019 analyzed the correlation of different cytokines including IL-6 and irAE during checkpoint inhibitor treatment of various cancers on a two to three weeks basis and identified that the irAE group (n = 16) had significantly elevated levels of five cytokines (IL-6, CXCL2, CCL20, CXCL8 and CCL23) compared to healthy controls [44]. Moreover, the authors stated that the increase in cytokines/chemokines at two-three weeks and at six weeks was significantly greater in the irAE group.…”
Section: Discussionmentioning
confidence: 99%
“…29 Although early reports of biomarkers predictive of irAEs are emerging, how these tests will be incorporated into real-world clinical management is not yet clear. 20,32 Any efforts at prevention of pneumonitis or other irAEs will also need to account for potentially detrimental effects of steroids. Although corticosteroid treatment once irAEs occur has not been linked with poorer disease control, up-front steroid exposure at the time of immunotherapy initiation does appear to be associated with inferior outcomes.…”
mentioning
confidence: 99%
“…In a similar study, a 40‐cytokine panel was applied pre‐ and post‐treatment with CPI [the majority (53 of 65) of these patients had lung cancer treated with anti‐PD‐1 therapy ( n = 49)] . They found that reduced baseline levels of several cytokines, in particular C‐X‐C motif chemokine ligand (CXCL)9, CXCL10, CXCL11 and CXCL13, were significantly associated with the development of irAEs.…”
Section: Prediction Of Immune Checkpoint Inhibitor‐related Toxicitymentioning
confidence: 99%
“… and Khan et al . , have used different methods, in different patient populations, once again making comparisons across studies challenging. Many of these studies describe changes in markers observed after, not before, exposure to checkpoint inhibitors.…”
Section: Limitationsmentioning
confidence: 99%